Analisis Swot Pembinaan Prestasi Cabang Olahraga Futsal SMA Negeri 9 Surabaya - Mochamat Rizki Setiawan; Achmad Widodo (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Coaching is a factor that plays an important role in getting better, and achievement is a benchmark for the success of a coaching. In the world of sports, especially futsal, futsal sports coaching needs to be done from an early age through talent search and guidance, breeding, education, and sports training. Therefore, the team needs to know its strengths and weaknesses and be able to identify opportunities and threats. This research was motivated by the ups and downs of futsal achievements at SMA Negeri 9 Surabaya and wanted to know based on SWOT analysis. This study aims to describe the coaching of futsal achievements at SMA Negeri 9 Surabaya based on the analysis of Strength, Weakness, Opportunity, and Threats (SWOT). This research is a qualitative descriptive research. The target of this study was 15 people consisting of 1 manager, 2 coaches, and 12 athletes. Data are obtained from interviews, observations, and documentation. Test the validity of the data using the source triangulation technique. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing / verification. The result of this study is that from antiquity, the strengths possessed outweigh, the weaknesses and the opportunities that exist are more than the threats. 1) The strengths possessed include management has been formed, sports management has been implemented, funding has been smooth and can be managed properly, athletes have high motivation and enthusiasm, team cohesiveness and confidence are increasing. 2) The weaknesses are outdoor or outdoor courts, management management is less conceptualized, and coaches do not have a coaching license. 3) The opportunity that exists is that routine championships have begun to be held again, the number of futsal teams between schools that stand makes competition tight, and athletes who excel in their fields. 4) There are concerns about insufficient athlete regeneration, and lack of funding from schools. Strategies that can be applied are optimizing and upgrading existing facilities & infrastructure, making budgets to be submitted to schools to get additional funds, maintaining and improving the quality and achievement of athletes, coaches must continue to innovate while improving.